Modeling sincerity behaviour in software agent environment - Nur Huda Binti Jaafar (2023)
The growth of autonomous products shows that this technology is gradually becoming a part of human life. They provide many benefits for humans in assisting the performance and management of tasks. Software agent technology is one that manifests the autonomous technology. As an autonomous product, the technology has the ability to animate rational agents to cooperate and work in teams. However, due to the inherent rationality of software agent systems, the agents maintain the selfish attitude which becomes a subject for thought to improve efficiency. One way is to enable agents to help its teammate that has the same goal. In this thesis, we study the attempt to instill ethical human behaviour in a software agent environment in order to improve the efficiency. Sincerity is one of the human behaviours that can be instilled in a software agent environment. Studies have shown that this human ethical behaviour has proven its benefits to human organizations. The instilling of sincerity in a software agent environment may help to promote teamwork in an agent community. Consequently, this research is focused on the study of instilling human sincerity in a software agent behaviour. The study involves conducting a survey to identify the factors related to human sincerity while performing tasks. We use the survey results to design the agent sincerity rules. The dynamic characteristic is one of the elements included in modelling the agent sincerity behaviour. For this purpose, we create three levels of agent sincerity: less sincere, moderate sincere and most sincere. These levels determine how an agent responds to its community while performing its tasks and how its sincerity level changes according to the merit points. In order to avoid imbalance of work burden between the agents, this study designs a Work Manager to evaluate the capability of agent in receiving and handling new tasks. An agent is not allowed to take up a new task if it does not fulfil the criteria of the Work Manager evaluation although it is at its most sincere level. The architecture of agent sincerity environment, the BDI of sincere agent and the flow of agent communications are the other parts that support the implementation of sincerity behaviour in the agent environment. We validate the model of agent sincerity behaviour by simulating the implementation of sincere agent behaviour using the JADE platform. The results of the simulation show that the instilling of sincerity in an agent environment reduces the selfish behaviour and increases the teamwork among the agents in the community. Incidentally, by having sincerity behaviour in their environment, it is found out that the productivity of agents are also improved.